Elucidating molecular lipid perturbations in trigeminal neuralgia using cerebrospinal fluid lipidomics - Dongyuan Xu; Xuan Dai; Qianwen He; Zhimin Mei; Yixuan Zhou; Jingwei Zhao; Nanxiang Xiong (Scientific Reports)
Abstract Trigeminal neuralgia (TN) is a neuropathic facial pain disorder characterized by severe stabbing pain along the trigeminal nerve. While its pathogenesis remains unclear, nerve demyelination and inflammation are likely involved. Current research has primarily focused on various blood-based omics approaches, which do not fully capture the lipid alterations occurring during TN progression in brain. In contrast, our study is the first to investigate cerebrospinal fluid (CSF) lipidomic profiles in TN patients, aiming to elucidate potential disease mechanisms. CSF samples were collected from 22 TN patients and 18 healthy controls, followed by untargeted lipidomic analysis using high-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry. A pipeline for lipid identification and relative quantification, combined with statistical analysis, revealed 188 lipid species across 21 classes. We found significant upregulation of Cer-NPs, LPCs, PCs, TGs, and OxTGs in TN patients, while stigmasterol hexoside was downregulated. Moderate correlations were observed between lipid species and clinical parameters. These findings highlight considerable CSF lipidome alterations in TN, suggesting roles for nerve demyelination, neuroinflammation, and pain sensitization in its pathogenesis. Our study provides novel insights into lipid targets that may offer therapeutic potential for managing TN.